Specific tyrosine phosphorylation of α7 nicotinic receptor modulates its ionotropic and metabotropic responses - Chrestia, Juan Facundo (2020)
The α7 nicotinic acetylcholine receptor in neurons is associated to neurological and neurodegenerative disorders. α7 is also expressed in glial and immune cells, where it plays a role in neuroprotection and inflammation. Protein phosphorylation is an important regulatory mechanism involved in physiological and pathological processes. We investigated the role of tyrosine phosphorylation of α7 in its dual ionotropic/metabotropic function. In cells expressing α7, singlechannel activity appears as brief isolated openings and episodes of few openings in quick succession (bursts). Inhibition of Src family kinases by PP2 as well as co-expression of α7 with an inactive Src kinase increase the duration and frequency of bursts, while inhibition of tyrosine phosphatases decreases open and burst durations without affecting channel amplitude. A mutant α7 lacking phosphorylation sites shows longer burst durations and insensitivity to PP2, thus revealing that the two tyrosine residues in the intracellular domain (ICD) are involved in receptor modulation. Cells exposed to a specific α7 agonist show an increase of ERK1/2 phosphorylation, which is detected neither in the presence of Src family kinases inhibitors nor in cells expressing the mutant receptor lacking tyrosines. Thus, phosphorylation negatively modulates ionotropic α7 activity probably by enhancing desensitization whereas the phosphorylated state of α7-ICD is required for the metabotropic receptor responses.